Eksistensi Generasi Muda dalam Menjaga Ketahanan Pangan Untuk Pembangunan Berkelanjutan: Studi di Desa Kadungrembug, Kabupaten Sidoarjo. - Ana Toni Roby Candra Yudha; Salsa Yuli Setiani; Nurul Huda; Maksum; Sugiyanto (Journal of Economics Development Issues, 2023)
This study was conducted to identify and analyze the importance of the role played by the younger generation in Kadungrembug Village's agricultural development to maintain food security and other fields relevant to agriculture. This research uses a descriptive qualitative analysis method. Data was predominantly obtained from primary data. most of them came from local residents aged 16-30 years and worked as farmers and non-farmers as well as village government officials. The results of this study indicate that the agricultural development of Kadungrembug Village has not been fully successful, even though there are many advanced technologies for managing rice fields. So the welfare of farmers is still not felt by Kadungrembug Village farmers. The role played by the younger generation towards Kadungrembug Village's agriculture has not been maximized due to the lack of awareness and literacy of the younger generation on the importance of loving domestic products. This can be seen from how often they use or consume local products such as tubers, local rice, and secondary crops. So, the corresponding suggestion is that the local Karang Taruna can get opportunities in various village forums, especially in empowerment and agriculture forums.